Pemberdayaan UMKM Melalui Platform E-Commerce Panduan Praktis Membuat Akun Shopee untuk Aries Craft Rajut - Akmal, Muhammad; Mutadhiroh, Fika Aprilia; Nisak, Indah Latifatun; Rohman, Ahmad Taufiqi; NurJihan, Salma; Noviyanti, Nurin Eka; Najih, Alvin; Mundhori, Mundhori (Welfare : Jurnal Pengabdian Masyarakat, 2024)
MSMEs play a significant role in the Indonesian economy, but many face challenges in utilizing digital technology to expand their markets. Aries Craft Rajut, a handicraft MSME, needs practical guidance to utilize e-commerce platforms such as Shopee in an effort to increase product visibility and sales. This community service activity aims to empower Aries Craft Rajut through training in creating and managing Shopee accounts. The implementation method includes direct assistance, preparation of technical guides, account creation simulations, and product uploads. Evaluation is carried out through monitoring the use of Shopee accounts and consumer interactions. The results show that participants are able to create accounts, upload products with attractive descriptions, and understand the promotional features on Shopee. This activity increases the digital literacy of MSME actors, expands market access, and strengthens business sustainability. Continuous assistance is proposed to ensure effectiveness and consistency in e-commerce account management.